1996
DOI: 10.1007/bf00419468
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the use of a starter culture in the fermentation of maize for ?kenkey? production in Ghana

Abstract: Controlled fermentation of maize was carried out using six strains of Lactobacillus fermentum and one strain of yeast, Saccharomyces cerevisiae, isolated from traditionally fermented maize dough as starter cultures for inoculum enrichement. The fermentations were monitored by pH, acidity, microbiological analysis and taste panel evaluation of two products, kenkey and koko, prepared from the fermented doughs. The strains of L. fermentum used as starter culture dominated the microflora during fermentation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 10 publications
4
27
1
Order By: Relevance
“…curvatus were also among the predominant species at the end of the fermentations. These results are in agreement with the generally accepted concept that traditional fermentations are dominated by a few microbial species that are selected during the course of fermentation as a result of physiological and metabolic adaptation to the food matrix [29,35]. The relative dominance of the homofermentative L. lactis over other bacteria may be due to its tolerance to low pH, which may reduce growth of heterofermentative LAB [45].…”
Section: Discussionsupporting
confidence: 90%
“…curvatus were also among the predominant species at the end of the fermentations. These results are in agreement with the generally accepted concept that traditional fermentations are dominated by a few microbial species that are selected during the course of fermentation as a result of physiological and metabolic adaptation to the food matrix [29,35]. The relative dominance of the homofermentative L. lactis over other bacteria may be due to its tolerance to low pH, which may reduce growth of heterofermentative LAB [45].…”
Section: Discussionsupporting
confidence: 90%
“…According to Hounhouigan et al (1993) and Halm et al (1996), L. fermentum has been found to be the predominant microorganism in fermented products of cereals. Calderon et al (2003) observed that this microorganism has the ability to use starch as a substrate by producing α-amylase and that it is classified as an amylolytic lactic acid bacteria (ALAB).…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation of maize dough in Ghana is traditionally spontaneous and largely uncontrolled. Attempts to standardize and improve quality as well reduce fermentation time of the Ghanaian maize dough have been carried out using starter cultures of some of the dominant microorganisms [4,5,6]. Similar studies have been done with other African fermented maize products.…”
Section: Introductionmentioning
confidence: 98%
“…The use of the dominant microorganisms, L. fermentum, S. cerevisiae and C. krusei in mixed combinations to serve as suitable starter cultures for acceptable and consistent quality characteristics of the Ghanaian fermented maize dough has been suggested by several authors [1,5,6,16,18]. In an earlier work, volatile compounds characterizing the aroma of Ghanaian fermented maize dough produced spontaneously and with the addition of single starter cultures of the dominant microorganisms were determined [19].…”
Section: Introductionmentioning
confidence: 99%